Pandangan Masyarakat Terhadap Arah Kiblat Masjid Besertifikasi Dari Kementrian Agama - Zaini Zaini; Istifianah Istifianah; Muthmainnah Muthmainnah (Universitas Cokroaminoto Yogyakarta, 2015)
Survey needs to be done for identifiying public opinion of the congregation of Masjid Al-Hidayah on the direction of Qiblah and its change. In a qualitative description, the data obtained through observation, documentation and FGD, were elaborated after content analysis. The congregation agreed that Qibla direction on facing the Qiblah to the west in performing prayers at their mosque becomes very important in prayer worship. This understanding is in accord with the MUI fatwa on the direction of Qibla. However, they are not in the same view in the needs of changing the direction of Qibla of the mosque. Therefore, the continuous dissemination of the qiblah understanding to the public is strongly advised, including changes that have no impact on the integrity building of the mosque.